2003
DOI: 10.1093/heapro/dag403
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control and gender in south-east Asia. Part II: Singapore and Vietnam

Abstract: In the World Health Organization's Western Pacific Region, being born male is the single greatest risk marker for tobacco use. While the literature demonstrates that risks associated with tobacco use may vary according to sex, gender refers to the socially determined roles and responsibilities of men and women, who initiate, continue and quit using tobacco for complex and often different reasons. Cigarette advertising frequently appeals to gender roles. Yet tobacco control policy tends to be gender-blind. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
71
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 4 publications
8
71
1
Order By: Relevance
“…13,19 The overall prevalence of smoking was nine times higher among men than women, but the gap is closing rapidly because of the dramatic increase in smoking rate among younger women. The smoking rates for men were 19.2, 12.6, 9, 8, and 3.8 times higher than for women at Ն 55 years, 45-55, 35-44, 25-34, and 18-24 year old, respectively (Table 1).…”
Section: Logistic Regressionmentioning
confidence: 99%
See 3 more Smart Citations
“…13,19 The overall prevalence of smoking was nine times higher among men than women, but the gap is closing rapidly because of the dramatic increase in smoking rate among younger women. The smoking rates for men were 19.2, 12.6, 9, 8, and 3.8 times higher than for women at Ն 55 years, 45-55, 35-44, 25-34, and 18-24 year old, respectively (Table 1).…”
Section: Logistic Regressionmentioning
confidence: 99%
“…13,14,20 In addition, earlier studies have shown that the tobacco industry intentionally targeted women by focusing on female-identified needs, preferences, and positive images of smoking, [21][22][23] although there are no conclusive studies of how the tobacco industry targets women and teenage consumers in Taiwan. More work should be done to monitor and decrease the impact of the trade liberalization and cigarette marketing on smoking in these minority groups.…”
Section: Logistic Regressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In East and South Asia, North Africa and the Middle East, men smoke much more than women [1], and it is possible that more traditional gender expectations and cultural norms about women may delay the uptake of tobacco use among women [11][12][13]. In these regions, men are clearly in stage II of the epidemic whereas women remain in stage I although use of smokeless tobacco is quite common in South Asia and more prevalent among persons of lower SEP.…”
mentioning
confidence: 99%